2015
DOI: 10.1016/j.rmed.2015.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Emphysema and DL CO predict a clinically important difference for 6MWD decline in COPD

Abstract: In COPD patients the burden of emphysema on CT scan and DLCO predict a clinically meaningful decline in exercise capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
38
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 42 publications
3
38
1
1
Order By: Relevance
“…By contrast, quantifying the severity of emphysema by DL CO is a more feasible method that can be performed simply at out-patient clinics with no harm to patients. As expected, previous data have shown that DL CO corresponded well with the CT emphysema score and predicted the risk of acute exacerbation, as well as the patients' exercise capacity (16,31). Our results also demonstrated that lower DL CO value was associated with acute exacerbation in univariate analysis ( Table 3).…”
Section: Discussionsupporting
confidence: 89%
“…By contrast, quantifying the severity of emphysema by DL CO is a more feasible method that can be performed simply at out-patient clinics with no harm to patients. As expected, previous data have shown that DL CO corresponded well with the CT emphysema score and predicted the risk of acute exacerbation, as well as the patients' exercise capacity (16,31). Our results also demonstrated that lower DL CO value was associated with acute exacerbation in univariate analysis ( Table 3).…”
Section: Discussionsupporting
confidence: 89%
“…In patients with COPD, MRI and CT can show changes in the muscle mass of lower limbs after a period of exercise 7 , 16 . Likewise, CT shows a high correlation between muscle thickness and the distance walked during the 6MWT 5 , 6 . Although CT is useful for evaluating the progression of muscular dysfunction in patients with COPD, 5 routine clinical use is limited because of economic costs.…”
mentioning
confidence: 99%
“…Besides airway obstruction, the changes of lung parenchymal structure, resulting in lung hyperinflation (air trapping) and gas exchange abnormalities, are also the key pathophysiologic processes during COPD progression. The corresponding functional studies suggest that lung volumetric parameters such as residual volume (RV) and total lung capacity (TLC) are important measurements in evaluating COPD severities and treatment responses67. However, a gold standard method to evaluate lung volumes has not yet been confirmed.…”
mentioning
confidence: 99%